Rapid changes in the surface carbonate system under complex mixing schemes across the Bering Sea: a comparative study of a forward voyage in July and a return voyage in September 2018 - Yang, Wei; Wu, Yingxu; Cai, Wei-Jun; Ouyang, Zhangxian; Zhuang, Yanpei; Chen, Liqi; Qi, Di (Frontiers in Marine Science, 2023)
Regulated by the rapid changes in temperature, mixing and biological production during warm seasons, surface carbonate system in Bering Sea is subject to significant spatial-temporal variability. However, the seasonal evolution of carbon cycle and its controls are less clear due to the lack of observations. Here we presented the carbonate data collected during a forward voyage in July and return voyage in September 2018 across the Bering Sea. During both voyages, we showed distinct dissolved inorganic carbon versus total alkalinity (DIC-TA) relationships and partial pressure of CO2 (pCO2) distribution patterns in the Southern Basin (54-57 °N), Northern Basin (57-59 °N), the Slope (59-61 °N), the Shelf (61-64 °N), and the Bering Strait (>64 °N). In the Southern Basin, Northern Basin, and the Slope, surface water was a two end-member mixing of Rainwater and the Bering Summer Water (BSW) during the forward voyage, while a two end-member mixing of North Pacific Surface Water (NPSW) and BSW during the return voyage. As a result, the observed DIC was almost consistent with the conservative mixing line with a slight DIC addition/remove of -8.6~5.8 µmol kg-1, suggesting the low biological production/respiration during both voyages. Seasonally, the higher factions of NPSW featured low pCO2 during the return voyage dominated the pCO2 drawdown from July to September in the Southern Basin and the Slope. On the shelf, the surface water was a two end-member mixing of plume water from Anadyr River and BSW during both voyages, but the decreased DIC consumption via biological production from 59.9±25.8 µmol kg-1 to 34.8±14.0 µmol kg-1 contributed to the pCO2 increase from July to September. In the Bering Strait, the coastal area was characterized by the influence of plume water from Anadyr River in July and the coastal upwelling in September. The high biological production in plume water made a strong CO2 sink during the forward voyage, while the upwelling of carbon-enriched subsurface water with minor DIC consumption made the coastal ecosystem a strong CO2 source during the return voyage.